Occupational Safety Climate and Hazards in the Industrial Sector: Gender Differences Perspective, Saudi Arabia - AlMousa, Norah; Althabet, Nadin; AlSultan, Sarah; Albagmi, Faisal; AlNujaidi, Heba; Salama, Khaled F. (Frontiers in Public Health, 2022)
Abstract Background: Recently, Occupational Health and Safety (OHS) has become a growing public health concern worldwide. A considerable body of literature has been generated around the theme of safety climate perceptions and occupational hazards, as many researchers have examined perceptions of the occupational safety climate in relation to organizational hierarchy. But there is an urgent need to address safety problems associated with gender differences, especially in Saudi Arabia, where women have only recently begun to work in the industrial field. Therefore, this study aims to assess workers’ perceptions of the safety climate and OHS hazards and identify gender differences among workers. Methods: A cross-sectional study was carried out, using the Nordic Occupational Safety Climate Questionnaire (NOSACQ-50) to assess seven dimensions of safety climate perception and a standardized structured questionnaire adapted from the National Institute of Occupational Health to assess occupational hazards. Results: The results indicated that respondents perceived only one dimension of their relevant occupational safety climates positively. This was “Peer safety communication, learning, and trust in co-workers”. Workers experienced a range of different occupational hazards in factories, with noise being the most common. There were significant differences between females and males in the areas of safety priority and risk non-acceptance. Women were more likely to experience ergonomic problems than their male counterparts. Conclusion: The present study concludes that industries need to comply with national and international OHS standards and rules, especially related to gender perspectives and hazards, as well as provide proper occupational health services in their factories.